Pengembangan Destinasi Pariwisata Gayo Lues Berbasis Integrasi Media Sosial - Safuridar, Safuridar; Andiny, Puti; Hardianti, Anisha (Lembaga Dongan Dosen, 2025)
The development of destination management and digital marketing skills aims to increase community income in Gayo Lues Regency through the tourism sector. The community's reliance on less effective traditional marketing methods and the underutilization of social media have highlighted the need for more efficient and impactful alternatives to promote local tourism destinations. This program is designed to educate local youth on the multiplier effect of tourism and train them in managing social media accounts and creating engaging promotional content using digital platforms such as TikTok, Instagram, Facebook, and YouTube. The approach used in this community service activity combines the Rapid Rural Appraisal (RRA) and Participatory Rural Appraisal (PRA) methods. RRA enables quick and efficient data collection by involving the community, while PRA encourages active community participation in problem analysis and solution development. Hands-on training and intensive mentoring will be provided to ensure that participants are capable of effectively managing and utilizing social media to promote their tourism destinations. It is expected that this program will not only increase local income through the tourism sector but also help foster a more competitive and sustainable tourism ecosystem. The final stage of the program involves mentoring and evaluation to measure the success of the community service initiative